Scaling properties of crack branching and brittle fragmentation - Uvarov S.; Leontiev V.; Naimark O.; Davydova M. (EPJ Web of Conferences, 2011)
The present study is focused on the correlation of scaling properties of crack branching and brittle fragmentation with damage accumulation and a change in the fracture mechanism. The experimental results obtained from the glass fragmentation tests indicate that the size distribution of fragments has a fractal character and is described by a power law.